S-Nitroso-L-Cysteine Stereoselectively Blunts the Deleterious Effects of Fentanyl on Breathing While Augmenting Antinociception in Freely-Moving Rats - Paulina M. Getsy; Santhosh M. Baby; Ryan B. Gruber; Benjamin Gaston; Tristan H. J. Lewis; Alan Grossfield; James M. Seckler; Yee-Hsee Hsieh; James N. Bates; Stephen J. Lewis; Stephen J. Lewis; Stephen J. Lewis (Frontiers Media S.A., 2022)
Endogenous and exogenously administered S-nitrosothiols modulate the activities of central and peripheral systems that control breathing. We have unpublished data showing that the deleterious effects of morphine on arterial blood-gas chemistry (i.e., pH, pCO2, pO2, and sO2) and Alveolar-arterial gradient (i.e., index of gas exchange) were markedly diminished in anesthetized Sprague Dawley rats that received a continuous intravenous infusion of the endogenous S-nitrosothiol, S-nitroso-L-cysteine. The present study extends these findings by showing that unanesthetized adult male Sprague Dawley rats receiving an intravenous infusion of S-nitroso-L-cysteine (100 or 200 nmol/kg/min) markedly diminished the ability of intravenous injections of the potent synthetic opioid, fentanyl (10, 25, and 50 μg/kg), to depress the frequency of breathing, tidal volume, and minute ventilation. Our study also found that the ability of intravenously injected fentanyl (10, 25, and 50 μg/kg) to disturb eupneic breathing, which was measured as a marked increase of the non-eupneic breathing index, was substantially reduced in unanesthetized rats receiving intravenous infusions of S-nitroso-L-cysteine (100 or 200 nmol/kg/min). In contrast, the deleterious effects of fentanyl (10, 25, and 50 μg/kg) on frequency of breathing, tidal volume, minute ventilation and non-eupneic breathing index were fully expressed in rats receiving continuous infusions (200 nmol/kg/min) of the parent amino acid, L-cysteine, or the D-isomer, namely, S-nitroso-D-cysteine. In addition, the antinociceptive actions of the above doses of fentanyl as monitored by the tail-flick latency assay, were enhanced by S-nitroso-L-cysteine, but not L-cysteine or S-nitroso-D-cysteine. Taken together, these findings add to existing knowledge that S-nitroso-L-cysteine stereoselectively modulates the detrimental effects of opioids on breathing, and opens the door for mechanistic studies designed to establish whether the pharmacological actions of S-nitroso-L-cysteine involve signaling processes that include 1) the activation of plasma membrane ion channels and receptors, 2) selective intracellular entry of S-nitroso-L-cysteine, and/or 3) S-nitrosylation events. Whether alterations in the bioavailability and bioactivity of endogenous S-nitroso-L-cysteine is a key factor in determining the potency/efficacy of fentanyl on breathing is an intriguing question.